Relationship between primary care visits and hospital admissions in remote Indigenous patients with diabetes: A multivariate spline regression model - Zhao, Y.; Connors, C.; Lee, Andy; Liang, Wenbin (Elsevier Ireland Ltd, 2015)
Aims - To determine if access to primary health care (PHC) is associated with reduced hospitalisations for remote Indigenous patients with diabetes. Methods - Using individual level linked health clinic and hospital data, a retrospective cohort study was conducted to estimate annual hospital admission rate by number of clinic visits in the Northern Territory of Australia, stratified by age group, sex and the presence of comorbidities. A spline regression model was used to describe the clinic-hospital relationship with covariates. An impact index of PHC visits was derived using the first derivative of the quadratic equations evaluated at the parameter estimates. Results -The relationship between PHC visits and hospitalisations in diabetes care appeared to be a U-curve. Low levels of PHC visits were associated with increased hospital admissions amongst people with diabetes. The overall level of all-cause hospitalisations for patients with diabetes was minimised when the PHC visits were 7.9 per person-year (95% confidence interval 5.8–10). Conclusions -Using existing empirical data, this study suggests that other things being equal, diabetes patients who had an adequate level of PHC visits are likely to have a lower level of hospitalisations than those with fewer or more PHC visits. This study highlights the importance for remote Indigenous patients with diabetes to have adequate access to PHC.